ANALYSIS OF MANGROVE FOREST VEGETATION ON MOLAS BEACH, BUNAKEN DISTRICT, MANADO CITY - Futwembun, Fransiska; Lawalata, Helen J; Setyawati, Iriani; Ogi, Nova L I M; Manampiring, Nonny; Mokosuli, Yermia (Indonesian Biodiversity Journal, 2024)
The lack of scientific information about the current condition of the mangrove ecosystem on the Molas beach in the Bunaken District of Manado City is an important reason to conduct a study related to the analysis of mangrove forest vegetation. The purpose of this research is to identify the types of mangroves and to find the Important Value Index (INP) of mangroves on the Molas beach in the Bunaken District of Manado City. Data collection was conducted using the line transect method with plots at only one observation station, which was then analyzed to determine the Importance Value Index (INP). Based on the observations, it was found that four types of mangroves were present at the research location. The dominant mangrove species are Bruguiera Cylindrica, Bruguiera gymnorrhiza, Aegiceras cosniculatum, and Ceriops tagal. The substrate condition, which is dominated by muddy sand, and the water quality parameters that affect mangrove growth generally still meet the standards for mangrove growth. The species Ceriops tagal has the highest values of Relative Density, Relative Frequency, and Relative Dominance, resulting in the highest INP. Meanwhile, the lowest INP was found in the species Bruguiera gymnorrhiza in the tree category